Sex-related disparities in obstructive coronary artery disease, percutaneous coronary intervention, and mortality in adults with cardiac arrest. (15th October 2018) - John, Jenine; Parikh, Puja B.; Thippeswamy, Ganesh; Kataya, Abdo; Loeb, Charles; Tran, Linh; Patel, Jignesh K.
Abstract: Objectives: Despite numerous advances in the delivery of resuscitative care, cardiac arrest (CA) continues to be associated with high morbidity and mortality. We sought to examine the association between sex and presence of obstructive coronary artery disease (CAD), percutaneous coronary intervention (PCI), and mortality in adults with CA. Methods: The study population included 208 consecutive patients hospitalized with CA who underwent resuscitation and subsequent coronary angiogram at an academic tertiary medical center. The primary outcome of interest was presence of obstructive CAD, defined as >1 coronary artery with >70% stenosis or >1 coronary bypass graft with >70% stenosis. Results: Of the study population, 150 patients (72%) were men and 58 (28%) were women. Women had a trend toward lower rates of obstructive CAD (69% vs 80%, p  = 0.09) and lower rates of multivessel CAD compared to their male counterparts, but no significant difference in rates of PCI (62% vs 53%, p  = 0.26). While rates of therapeutic hypothermia and vasopressor requirement were similar in men and women, women were less likely to require percutaneous left ventricular support. In-hospital mortality rates were similar in men and women (23% vs 21%, p  = 0.68). In multivariate analysis, sex was not independently associated with obstructive CAD or mortality. Conclusions: In this observational contemporary study of adults with CA undergoing coronary angiogram, although women had a trend toward lower rates of obstructive CAD, no significant difference in rates of PCI and in-hospital mortality were noted between men and women. Highlights: In adults with cardiac arrest undergoing coronary angiogram, no significant differences in clinical presentation were noted in men and women. Women had a trend toward lower rates of obstructive coronary artery disease (CAD) and lower rates of multivessel CAD. Rates of percutaneous coronary intervention and mortality in men and women were similar.